Ensuring that biomedical engineers are ready for the real world. - Enderle, J.D (IEEE Engineering in medicine and biology magazine)
Discusses preparing biomedical engineering students for real-world problem solving by putting theory into practice in the curriculum. It is concluded that mechanisms for preparing biomedical engineering students for real-world problem solving are numerous. Failure to incorporate such real-world experiences throughout the curriculum creates frustration for the student, particularly for the freshman or sophomore undergraduate who lacks the experience to draw a connection between theory and practice. Upon graduation, the biomedical engineer is suddenly confronted with real-world problems and design challenges that require a team of experts, project planning and execution, regulatory and quality control, financial support, and a satisfied customer. Too often, graduates are unprepared for this transition to real-world engineering.